Microdomains of distinctive glycoprotein composition in the kidney proximal tubule brush border (The Rockefeller University Press, 1984)
Two membrane proteins, maltase and gp330 (the pathogenic antigen of Heymann nephritis), present in the proximal tubule brush border have recently been independently purified and found to be large glycoproteins of similar molecular weight (Mr = approximately 300,000) by SDS PAGE. To determine the relationship between the two, monoclonal antibodies raised against the purified proteins were used for comparative immunochemical analyses and immunocytochemical localization. When a detergent extract of [35S]methionine-labeled rat renal cortex was used for immunoprecipitation with monoclonal antimaltase IgG, a single band of approximately 300 kdaltons was precipitated, whereas a single 330-kdalton band was precipitated with monoclonal anti-gp330 IgG. Monoclonal antimaltase (gp300) IgG also immunoprecipitated maltase activity from solubilized renal maltase preparations, whereas monoclonal anti-gp330 IgG failed to do so. When cyanogen bromide-generated peptide maps of the two proteins were compared, there were many similar peptides, but some differences. When maltase and gp330 were localized by indirect immunofluorescence and by indirect immunoperoxidase and immunogold techniques at the electron microscope level, they were found to be differently distributed in the brush border of the initial (S1 and S2) segments of the proximal tubule: maltase was concentrated (approximately 90%) on the microvilli, and gp330 was concentrated (approximately 90%) in the clathrin-coated apical invaginations located at the base of the microvilli. We conclude that maltase (gp300) and the Heymann nephritis antigen (gp330) are structurally related membrane glycoproteins with a distinctive distribution in the proximal tubule brush border which may serve as markers for the microvillar and coated microdomains, respectively, of the apical plasmalemma.